Potential of Some Medicinal and Fodder Crops to Alleviate Soil Sickness in the Old Prunus persica var. Persica (L.) Batsch and Malus domestica Borkh. Tree Monocultures - Didyk, Nataliya; Ivanytska, Bogdana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
The effect of nine species of cover crops (calendula, eastern galega, tartary buckwheat, mustard, tansy phacelia, lemon balm, golden marigold, sainfoin, blue fenugreek) on allelopathic and biochemical characteristics of the rhizosphere soil from-under 30-year-old Malus domestica Borkh. and Prunus persica var. persica (L.) Batsch plantations in model laboratory experiments were studied. The samples of the rhizosphere soil were collected at the beginning of the growing season (fruit trees bud development), dried, sieved and placed into the plastic pots. The seeds of the tested cover crops were sown into the pots. After the emergence of the seedlings 10 plants per pot were left and cultivated for 4 months under laboratory conditions. The contents of the nutrients, organic carbon and soil acidity were determined at the beginning of the experiments. Every two weeks after the start of the experiments, the allelopathic activity of the soil was assessed using bioassays on the cress root growth and radish seeds germination. The number of free phenolics in soil solution was determined at the beginning and the end of the experiments. Analysis of the content of soil nutrients showed that the content of manganese and iron 3–6-fold exceeded the optimum level, and the content of free phenolics in soil solution exceeded the phytotoxic threshold almost 10-fold. Growing of cover crops improved the allelopathic and biochemical regime of the studied soil. The most effective were Tagetes tenuifolia, Phacelia tanacetifolia, and Sinapis alba. The size of the positive effect was correlated with the duration of cultivation of the cover crops in the soil. We consider the above-mentioned plant species promising for further study of their potential to restore soil fertility in the old apple and peach orchards.